1991
DOI: 10.1159/000150211
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of Potyviruses: Current Problems and Some Solutions

Abstract: There are two major requirements for potyvirus taxonomy; group-specific criteria and criteria which discriminate between distinct viruses and strains. This review discusses the relative merits in potyvirus taxonomy of molecular parameters, such as gene sequence data, nucleic acid hybridization, coat protein sequence data, or high-performance liquid chromatography peptide profiles, and phenotypic characteristics, such as particle morphology, host range, symptomatology, cross-protection, cytoplasmic inclusion mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
117
2
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(122 citation statements)
references
References 93 publications
2
117
2
1
Order By: Relevance
“…Potyviruses, the largest and most destructive group of plant viruses (Ward & Shukla, 1991), have a single-strand plus-sense RNA genome of about 10 kb with a single open reading frame (ORF). The translation product of this ORF is processed by three virus-encoded proteinases to yield a CP and at least seven non-structural proteins (Riechmann et al, 1992 ;Dougherty & Semler, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Potyviruses, the largest and most destructive group of plant viruses (Ward & Shukla, 1991), have a single-strand plus-sense RNA genome of about 10 kb with a single open reading frame (ORF). The translation product of this ORF is processed by three virus-encoded proteinases to yield a CP and at least seven non-structural proteins (Riechmann et al, 1992 ;Dougherty & Semler, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Based on preliminary investigations it was confirmed that the virus belongs to Potyvirus group of family Potyviridae. The potyvirus group (named for its prototypical member, potato virus Y (PVY)) is the largest of the 34 plant virus groups and families currently recognised [12]. This group contains at least 180 definitive and possible members (30% of all known plant viruses) which cause significant losses in agricultural, pastural, horticultural and ornamental crops [12].…”
Section: Discussionmentioning
confidence: 99%
“…The potyvirus group (named for its prototypical member, potato virus Y (PVY)) is the largest of the 34 plant virus groups and families currently recognised [12]. This group contains at least 180 definitive and possible members (30% of all known plant viruses) which cause significant losses in agricultural, pastural, horticultural and ornamental crops [12]. This is for the first time that potyvirus infecting Wedelia trilobata have been reported from Aligarh India.…”
Section: Discussionmentioning
confidence: 99%
“…Changes at positions 2809 and 3065 occur within the N-and C-terminal regions of the CP, which are known to be highly variable among potyviruses. But the change from methionine in strain G2 to isoleucine in G7 at amino acid position 3018 occurs within the trypsinresistant core, which displays significant amino acid identity among all potyviruses examined (Ward & Shukla, 1991). A recent report has shown that a change from glycine to proline in the virus CP correlates with ability of a strain of potato virus X to overcome resistance (Kohm et al, 1991).…”
Section: Discussionmentioning
confidence: 99%